Levering proteomic analysis of Pseudomonas fluorescens mediated resistance responses in tomato during pathogenicity of Fusarium oxysporum f. sp. oxysporum - Paranthaman, Lakshmidevi; Seethapathy, Parthasarathy; Pandita, Deepu; Gopalakrishnan, Chellappan; Sankaralingam, Subbiah; Venkatesh, Sakthivel; Malaisamy, Arunkumar; Pandita, Anu; Casini, Ryan; Alataway, Abed; Dewidar, Ahmed Z.; Almutairi, Khalid F.; et al. (Frontiers in Sustainable Food Systems, 2023)
The tomato, one of the world’s most extensively cultivated and consumed vegetable crops is negatively impacted by various pathogens. This study aimed to observe the differentially expressed proteins in tomato samples in plant–pathogen-biocontrol interactions. The fungal pathogen associated with wilted plants were isolated and identified based on its morphological and molecular characteristics. Fourteen strains of Pseudomonas fluorescens from agricultural soils were identified and described using biochemical assays, molecular analyses, and screening for antagonistic ability against the Fusarium wilt pathogen. Results demonstrated that the potential of P. fluorescens (TPf12) positively influenced the expression of antagonism against tomato wilt disease. A total of 14 proteins expressed differently were revealed in the 2D-PAGE-MS investigation. Proteins such as nucleoside diphosphate kinase, phenylalanine ammonia-lyase, protein kinase family protein, Ser/Thr protein kinase-like are unchanged in FOL pathogen interaction, but up-regulated in FOL + TPf12 treated roots, and lipid transfer-like protein, and phenylalanine ammonia-lyase were down-regulated in FOL infested roots and upregulated in FOL + TPf12 treated tomato roots. Phenylalanine ammonia-lyase protein expression is commonly found in TPf12 bioenriched roots, and FOL + TPf12 treated roots, indicating its role in response to the application of TPf12 in tomato. A GC–MS analysis was performed to detect the bioactive metabolites synthesized by TPf12. Molecular docking investigations were conducted using the maestro’s GLIDE docking module of the Schrodinger Software program. Among the secondary metabolites, Cyclohexanepropanoic acid, 2-oxo-, methyl ester (CAS), and 3-o-(4-o-Beta-D-Galactopyranosyl-Beta-D-Galactopyraosyl)-2-Acetylamino-2-Deoxy-D-Galactose were shown to be top-ranked with a least docking score against each differently expressed proteins. The profiled molecules expressed differently due to plant-pathogen-biocontrol interactions may be directly or incidentally involved in the wilt disease resistance of tomato plants.